Effects of brushing and immersion in denture cleanser on the surface roughness of polymethyl methacrylate - Agnes Victoria Kurniawan; Octarina; Hernindya Dwifulqi (Wolters Kluwer Medknow Publications, 2019)
Background: The proper method for cleaning dentures is important to prevent an increase in the surface roughness average (Ra). An average roughness value above 0.2 μm can increase bacterial colonization. Objective: The aim of this study was to investigate the effects of brushing and immersion in denture cleanser on the surface roughness of polymethyl methacrylate (PMMA) materials. Methods: Fifty PMMA samples (18 mm × 10 mm × 2 mm) were randomly divided into five groups (n = 10 each): immersion in distilled water (Group A), brushing without toothpaste (Group B), brushing with toothpaste (Group C), immersion in denture cleanser and brushing without toothpaste (Group D), and immersion in denture cleanser and brushing with toothpaste (Group E). The surface roughness was measured using a surface roughness tester before and after the treatment. The results were obtained by calculating the difference between the initial and final surface roughness values. The data were analyzed using Welch's one-way analysis of variance and the Games-Howell post hoc test. Results: The mean Ra values were 0.033 ± 0.024 μm for Group A, 0.057 ± 0.018 μm for Group B, 1.551 ± 1.234 μm for Group C, 0.102 ± 0.026 μm for Group D, and 1.695 ± 1.158 μm for Group E. There were statistically significant differences among the groups, with the exception of Groups A and B and Groups C and E. Conclusion: Brushing without toothpaste had the least effect on increasing the surface roughness, whereas brushing with toothpaste and immersion in denture cleanser greatly increased the surface roughness.